2020
DOI: 10.1111/os.12787
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Posttraumatic Elbow Stiffness Due to Soft Tissue Problems

Abstract: Objectives: To evaluate the effectiveness of arthroscopic management of posttraumatic elbow stiffness due to soft tissue problems. Methods: A retrospective review of 30 consecutive arthroscopic elbow releases for posttraumatic stiff elbow from November 2011 to December 2019 was conducted. Stiff elbows with bony problems, such as heterotopic ossification, intraarticular nonunion or malunion, and cartilage lesions were excluded from this study. Contracture and adhesion of soft tissue around the elbow were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“… 7 , 22 ROM increases have been reported up to over 100°, with multiple authors reporting improvements in functional outcomes scores over time. 5 , 23 , 24 Our cohort received an average 35° of improvement in the arc of motion by 6 months postoperatively, which is less than many studies reported in the literature. One explanation for this is that our cohort had higher preoperative flexion values than patients in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 76%
“… 7 , 22 ROM increases have been reported up to over 100°, with multiple authors reporting improvements in functional outcomes scores over time. 5 , 23 , 24 Our cohort received an average 35° of improvement in the arc of motion by 6 months postoperatively, which is less than many studies reported in the literature. One explanation for this is that our cohort had higher preoperative flexion values than patients in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 76%
“…Strategies to prevent contracture following arthroscopy include preoperative evaluation of risk factors and to address those that may be modifiable, establish optimal motion intraoperatively, limit postoperative inflammation, and initiate physical therapy and ROM exercises as early as possible. 67…”
Section: Stiffness/contracturementioning
confidence: 99%
“…Studies have shown improvement in ROM after active and passive exercises and continuous passive motion during the recovery process. 33,67 In addition, it has been found that loss of ROM is more likely to occur in elbows with posttraumatic disorders or patients with underlying conditions of arthritis and obesity. In one study, Werner et al 50 found that postoperative stiffness was significantly greater in obese patients (suggesting that preoperative counseling is imperative in this patient population.…”
Section: Stiffness/contracturementioning
confidence: 99%
“…Flexion/extension, varus/valgus, and pronation/supination are involved in controlling the spatial positions of the forearm and hand. The elbow is also notorious for being the most prone to stiffness after injury or surgery 1,2 . In order to adapt to modern lifestyles, a range of motion (ROM) of approximately 120° in flexion‐extension (from 27° ± 7° flexion to 149° ± 5° flexion) and another ROM of approximately 120° in pronation‐supination (from 20° ± 18° pronation to 104° ± 10° supination) are necessary, which may be greater than previously reported 3 .…”
Section: Introductionmentioning
confidence: 99%